2019
DOI: 10.1177/2325967119875139
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes After Isolated and Combined Posterior Cruciate Ligament Reconstruction in a Military Population

Abstract: Background: The rates of return to full activity, persistent disability, complications, and surgical revisions after operative management of posterior cruciate ligament (PCL) tears in a physically active population have not been reported. Purpose: To evaluate the clinical outcomes of active military patients with symptomatic PCL tears who underwent surgical reconstruction and compare outcomes between isolated PCL and multiligament injuries. Study Design: Cohort study; Level of evidence, 3. Methods: Individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…A failure rate of 1–25% after primary PCL-R is reported, mounting to 45% if unfavorable patient-reported outcomes (Knee Injury and Osteoarthritis Outcome Score < 40 points) are considered as subjective failure [ 4 , 36 , 41 , 46 , 81 , 88 ]. However, inadequate reporting and varying definitions of failures require caution in the interpretation of failure rates.…”
Section: Indications For Pcl-rmentioning
confidence: 99%
See 2 more Smart Citations
“…A failure rate of 1–25% after primary PCL-R is reported, mounting to 45% if unfavorable patient-reported outcomes (Knee Injury and Osteoarthritis Outcome Score < 40 points) are considered as subjective failure [ 4 , 36 , 41 , 46 , 81 , 88 ]. However, inadequate reporting and varying definitions of failures require caution in the interpretation of failure rates.…”
Section: Indications For Pcl-rmentioning
confidence: 99%
“…Failures after primary PCL-R are reported to cause severe impairments in daily living and are a burdening condition for most patients [ 41 , 58 , 59 , 81 ]. In such cases, a revision PCL-R is required and is sometimes considered as a salvage procedure.…”
Section: Clinical Outcomes Following Pcl-rmentioning
confidence: 99%
See 1 more Smart Citation
“…It emphasizes poorly measured and reported complications because none of the primary studies reported on graft failure rates or revision or rerupture rates despite the reported graft failure rates of 11.6% and 12.6% mentioned in other studies. 5,6 Only the study by Wang et al 26 reported on an overall complication rate but without statistical testing. It seems that the reported complications are related to graft harvesting and do not capture all relevant complications.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 3 PCL reconstruction as first-line routine care is still debated 4 because surgical intervention is not without its own challenges; there is a reported graft failure rate of 11.6% (range of 2.3%-30%) 5 and a revision rate of 12.6% in a highly active military population. 6 Complications such as rerupture or graft failures due to technical errors, including poor graft size, inadequate graft strength and improper placement of the tibial or femoral tunnels, 7 , 8 have been reported. Significant improvements were observed in post-PCL reconstruction functional scores and knee stability, although this seems to be valid only for moderate levels of activity and a fair return to sport level.…”
mentioning
confidence: 99%